2013
DOI: 10.3762/bjnano.4.49
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin probe force microscopy of nanocrystalline TiO2 photoelectrodes

Abstract: SummaryDye-sensitized solar cells (DSCs) provide a promising third-generation photovoltaic concept based on the spectral sensitization of a wide-bandgap metal oxide. Although the nanocrystalline TiO2 photoelectrode of a DSC consists of sintered nanoparticles, there are few studies on the nanoscale properties. We focus on the microscopic work function and surface photovoltage (SPV) determination of TiO2 photoelectrodes using Kelvin probe force microscopy in combination with a tunable illumination system. A comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 64 publications
4
22
2
Order By: Relevance
“…Stable trapping of electrons in trap states of the porous ZnO electrode, which are subject to only quite slow recombination or transfer to electron acceptors like O 2 or water from air governed by diffusion of the electrons within the porous semiconductor is, thereby, indicated. A similar time‐scale was reported for the decay of the photovoltage derived from KPFM measurements under comparable conditions at porous TiO 2 electrodes sensitized by the Ruthenium complex N719 . The signal was reported to have relaxed to the dark value within (43 ± 4) s. If we assume that the signal had relaxed to about 1% of its original value within that time, a lifetime of (9.3 ± 0.9) s would result, a value of very similar magnitude to the value of τ 3 determined in the present study.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Stable trapping of electrons in trap states of the porous ZnO electrode, which are subject to only quite slow recombination or transfer to electron acceptors like O 2 or water from air governed by diffusion of the electrons within the porous semiconductor is, thereby, indicated. A similar time‐scale was reported for the decay of the photovoltage derived from KPFM measurements under comparable conditions at porous TiO 2 electrodes sensitized by the Ruthenium complex N719 . The signal was reported to have relaxed to the dark value within (43 ± 4) s. If we assume that the signal had relaxed to about 1% of its original value within that time, a lifetime of (9.3 ± 0.9) s would result, a value of very similar magnitude to the value of τ 3 determined in the present study.…”
Section: Resultssupporting
confidence: 86%
“…It was related to electron diffusion within the porous semiconductor network among individual grains. A faster relaxation component not quantified in that study was assigned to electron transport within individual grains . Despite a different character of the electrodeposited ZnO as opposed to granular TiO 2 such assignment of τ 2 = 73 ms in the present study to electron transport within crystalline domains appears a reasonable assignment.…”
Section: Resultscontrasting
confidence: 48%
“…Thus, the increase in net dipole moments may be attributed to the formation of the polar molecules, that is, the polar β phase. In general, the change in the surface potential (Δ V ) is defined through the Helmholtz equation ( 40 )normalΔitalicV=4normalπitalicNP0cosfalse(normalθfalse)italicAnormalεwhere A is the surface area, N is the number of molecules, P is the dipole moment, P 0 is the dipole moment of the free molecule in a vacuum, θ is the molecular tilt angle, and ε = ( P 0 / P ) is the effective dielectric constant of a molecular monolayer. The surface potential changes of Δ V = −214 mV for pristine PVDF and Δ V = +416 mV for PVDF-G18 result in the dipole moments of 1.26 and 3.41 D with opposite directions, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 The electron injection might also be influenced by the resulting dipole moment normal to the surface. 8 Density functional theory (DFT) calculations have further shown that the interfacial dipole can change the position of the TiO 2 conduction band, which has direct influence on the open circuit voltage of DSCs. 9,10 In a real device, several anchoring geometries are possible, due to the fact that they are often based on mesoporous substrates with different crystallographic surfaces and defects.…”
Section: Introductionmentioning
confidence: 99%